Hablando con y sobre políticos en Twitter: un análisis de tweets que contienen menciones de candidatos en las elecciones presidenciales brasileñas - Medeiros, Débora Maria Moura; Bastian, Mariella; Trilling, Damian (Revista Latinoamericana de Opinión Pública, 2016)
While Twitter has become an increasingly important platform for public opinion formation, little is known about its use in recent Latin American election campaigns. We therefore investigate the case of the presidential elections in Brazil in October 2014, in order to analyze communication structures in actual and para-social interactions with presidential candidates. In particular, while Twitter makes it easy for ordinary citizens to express their opinion online, it is maybe even more important that they can also address and communicate with persons who would otherwise not be reachable at all. Politicians are probably the most important group in this regard. Based on N = 1,891,657 tweets containing an @mention of a candidate in the Brazilian elections of 2014, we investigate which actual or para-social interactions with the candidates take place. Furthermore, because framing literature suggests that all actors involved in a discussion on social media will try to highlight specific aspects and interpretations of issues and events, we used techniques of co-word analysis to investigate the ways in which the main candidates were framed by the Twitter users. The results give insight into the deliberative potential of Twitter: they show how the candidates are presented to the social media community and thus how this presentation may be reflected in public opinion.